Modeling malicious multi-attacker node collusion in MANETs via game theory - Khan, Burhan Ul Islam; Olanrewaju, Rashidah Funke; Matoo, Mohd Mueen Ul-Islam; Abdul Aziz, Afza; Ahmad Lone, Sajaad (IDOSI Publications, 2017)
Althoughthe mitigation approaches towards securing the mobile adhoc networks against malicious nodes have been explored widely in recent years but there is a dearth of solutions that can prove effective in addressing the behavior of malicious nodes within a network. As a result, visualizing the malicious nodes effectively through various simulation techniques is considered to be the most challenging issue. Owing to the fact that malicious nodes do not employ any such approaches that are probable to be detected, they show confusing behavior which makes it nearly impossible to distinguish them as malicious or regular nodes. The proposed study highlights the ability of game theory for enhancing the multi-attacker collusion approach to represent the unpredictable behavior of nodes in cooperating, reporting, declining or attacking other nodes to achieve effective modelling of the range of mobile nodes in a mobile adhoc network.